LOOKING AT THE HISTORY OF THE NATION THROUGH SPIRITUAL ETHICAL EDUCATION. - Oltiboyev Asqad Eshdavlatovich; Odilova Mavluda Uchqun qizi (Scholar Express Journal, 2023)
In this article, the ideological ideas and the place of women in them from the point of view of periods, stages and system of modern literature are analyzed scientifically, philosophically, and didactically.
Keywords: Jadid; enlightenment; reformism; development